Mengembangkan Kecerdasan Emosional dan Kecerdasan Spiritual Pada Diri Siswa - Zaini, Bahruddin; Hakim, Lukman (CENDEKIA: Jurnal Studi Keislaman, 2023)
Emotional and spiritual intelligence become two aspects or dimensions which is very, very important in developing a holistic person and comprehensive. The two are not only understanding and self-interaction own but also deep involvement that interacts and communication with other people and the surrounding world. Intelligence Emotional can be developed with the ability of intelligence from stimuli captured by human feelings themselves, While the development of spiritual intelligence can be realized by self-awareness of man as a weak creature and requires power to be abstract beyond human reason. This research highlights how both  mutually reinforces the foundations of personal balance. Result Research shows that humans who have levels High emotional intelligence is likely to have good interpersonal skills, they are able to build harmonious relationships, and can solve problems in his life, while spiritual intelligence enriches this dimension by providing depth and meaning in the experience Life.